Catalyst: reimagining sustainability with and through fine art - Angela Connelly (Resilience Alliance, 2016)
How might we begin to explore the concept of the "sustainable city" in a world often characterized as dynamic, fluid, and contested? Debates about the sustainable city are too often dominated by a technological discourse conducted among professional experts, but this technocratic framing is open to challenge. For some critics, sustainability is a meaningless notion, yet for others its semantic pliability opens up discursive spaces through which to explore interconnections across time, space, and scale. Thus, while enacting sustainability in policy and practice is an arduous task, we can productively ask how cultural imaginations might be stirred and shaken to make sustainability accessible to a wider public who might join the conversation. What role, we ask, can and should the arts play in wider debates about sustainability in the city today? We explore a coproduced artwork in the northeast of England in order to explain how practice-led research methods were put into dialogue with the social sciences to activate new perspectives on the politics, aesthetics, and practices of sustainability. The case is presented to argue that creative material experimentations can be used as an active research inquiry through which ideas can be tested without knowing predefined means or ends. The case shows how such creativity acts as a catalyst to engage a heterogeneous mix of actors in the redefinition of urban spaces, juxtaposing past and present, with the ephemeral and the (seemingly) durable.